Influence of EAPI Skills Training Course on the Knowledge, Attitude, and Practice of Undergraduate University Students: A Case of the EAPI Program, Uganda - Kigozi, Julia; Baidhe, Emmanuel; Muzira Mukisa, Ivan; Muyanja, Charles; Namubiru, Leatitiah; Katarikawe, Brenda (International Journal of Learning and Development, 2021)
Upon employment, fresh graduates have been widely criticized for their underperformance due to their lack of relevant practical skills. Furthermore, students need training that allows them to blend knowledge with the practice in the workspace. This study assessed the influence of an ‘Empowerment of the Agro-processing Industry (EAPI)' skills training for the agro-processing industry, on the knowledge, attitude, and practice among students in the School of Food Technology Nutrition and Bio-Engineering (SFTNB), Makerere University. Students were trained in 8 modules including; food process and value-chain management, food product optimization, national and international standards of food products, application of good management practices (GMP) and hygienic food processing, quality control in food production processes, waste management, infrastructure development to meet quality & production capacity in food production facilities and food product marketing & preparation for export markets. A semi-structured questionnaire with a descriptive, scale and thematic analysis was used to evaluate the impact of the training. The reliability of the responses of the questionnaires was tested using Cronbach’s alpha and they showed high reliability; yielding values that ranged between 0.88 and 0.97. Results showed a statistically significant difference (p < 0.05) in knowledge, attitude and practice for product optimization, adequate processing facility, standardization, certification, and export marketing. Cronbach’s alpha values ranged between 0.88 and 0.97 for all stated variables indicating that the scales were sound and reliable. Therefore, the inclusion of similar study material into the current curriculum would help improve and enrich the curriculum thereby producing well-prepared students for the food processing industry in Uganda.
Keywords: Short off-the-job training; Students; Knowledge; Practice; Food processing industry; Uganda